CRISIS MONITORING THE FINANCIAL CONDITION OF AGRICULTURAL ENTERPRISES - Дорогань-Писаренко, Л. О. (Scientific Progress & Innovations, 2014)
Reviewed existing approaches to assessing the financial performance of agricultural enterprises. The features of the implementation of anti-crisis monitoring in modern conditions. Noted the need to improve the methodological approaches to the assessment of the financial situation of agricultural enterprises and the need to implement measures for improvement of business entities, with signs of the crisis.